Birthweight and blood pressure among children in Harare, Zimbabwe. Issue 2 (1st September 1998) - Woelk, Godfrey; Emanuel, Irvin; Weiss, Noel S; Psaty, Bruce M
Abstract : AIM: To determine whether poor uterine growth may be associated with increased blood pressure and subsequent hypertension in adulthood. METHODS: A retrospective cohort study of 756 schoolchildren (mean age 6.5 years) was carried out in six low income areas in Harare city, Zimbabwe. Indices of intrauterine growth and blood pressure were assessed. RESULTS: Adjusted for current weight, the children's systolic blood pressure was inversely related to their birthweight; for each decreasing kg of birthweight, systolic blood pressure rose by 1.73 mm Hg (95% CI; 0.181 to 3.28). After adjustment for current weight, systolic blood pressure was also inversely associated with occipito-frontal circumference, but not with birth length or gestational age. Diastolic blood pressure was not associated with any of the intrauterine indices. CONCLUSION: Fetal size may be inversely related to systolic blood pressure in childhood in an African population.